Analisis Pemilihan Buku Teks Sejarah dalam Pemanfaatan Sebagai Sumber Belajar Untuk Siswa/Siswi di SMA Swasta Rakyat - Fiqri Haiqal; Surya Aymanda Nababan; Benny Junior Kaban; Aditya Darma; Fikri Alkhairi (Universitas Islam Sumatera Utara, 2023)
History books play an important role in history learning because they provide information and explanations about important historical events. However, choosing the right textbook is an important factor in ensuring the effective use of textbooks as learning tools. The research method used is literature research by collecting and analyzing history textbooks available and used at Pancur Batu People's Private High School. The results of the analysis show that in choosing a good history textbook should pay attention to the accuracy of the information presented. Textbooks must contain accurate historical facts and be supported by valid evidence. In addition, textbooks must be in accordance with the applicable curriculum of Pancur Batu People's Private High School so that they contain relevant material and support the achievement of narrative learning objectives. Ease of reading is also an important factor when history textbooks have to be written in a language that students can easily understand. /Student. The use of images, charts, and graphs can also help students better understand historical content. In addition, a good history textbook should provide multiple perspectives to help students understand multiple perspectives on historical events. Finally, the importance of history books to students' lives is very important. History textbooks that connect the material to students' current reality or experience can increase their interest and participation in history learning. By considering these factors, the selection of the right history textbook at Pancur Batu People's Private High School can provide effective and quality learning resources for students. The importance of this research lies in the importance of selecting quality history textbooks to enhance students' understanding of history and develop critical thinking.